“Popping the Ion‐Basket”: Enhancing Thermoelectric Performance of Conjugated Polymers by Blending with Latently Dissociable Perovskite Quantum Dots - Hansol Lee; Hoimin Kim; Haedam Jin; Seungju Kang; Tae Woong Yoon; Dongki Lee; Guobing Zhang; Min Kim; Boseok Kang (Advanced Science)
Abstract A novel additive method to boost the Seebeck coefficient of doped conjugated polymers without a significant loss in electrical conductivity is demonstrated. Perovskite (CsPbBr3) quantum dots (QDs) passivated by ligands with long alkyl chains are mixed with a conjugated polymer in a solution phase to form polymer‐QD blend films. Solution sequential doping of the blend film with AuCl3 solution not only doped the conjugated polymer but also decomposed the QDs, resulting in a doped conjugated polymer film embedded with separated ions dissociated from the QDs. For the doped polymer‐molten QD blend films with the optimal QD content, it is found that a greatly enhanced Seebeck coefficient is achieved compared to that of the doped polymer film without QDs, while the doping level and electrical conductivity are not significantly reduced by the QD incorporation. Consequently, the power factor is enhanced, reaching a remarkably high value of up to 401.9 µW m−1 K−2 (≈155% increase with the QDs). The applicability of this method to a variety of conjugated polymers is also demonstrated. The enhancement in the Seebeck coefficient is attributed to ion‐induced local variations in the polymer work function, which generates an internal energy barrier for charge transport and causes an energy filtering effect.